Long-term stability of phase-separated half-Heusler compounds. Issue 44 (21st October 2015) - Krez, J.; Balke, B.; Ouardi, S.; Selle, S.; Höche, T.; Felser, C.; Hermes, W.; Schwind, M.
Abstract : The long-term stability of n- and p-type thermoelectric half-Heusler materials is investigated. The dendritic microstructure is temperature resistant and maintained the low thermal conductivity values ( κ < 4 W m −1 K −1 ) even after 500 heating and cooling cycles. Abstract : Half-Heusler (HH) compounds have shown high figure of merit up to 1.5. Here, we address the long-term stability of n- and p-type HH materials. For this purpose, we investigated HH materials based on the Ti0.3 Zr0.35 Hf0.35 NiSn-system after 500 cycles (1700 h) from 373 to 873 K. Both compounds exhibit a maximum Seebeck coefficient of | α | ≈ 210 μV K −1 and a phase separation into two HH phases. The dendritic microstructure is temperature resistant and upon cycling the changes in the microstructure are so marginal that the low thermal conductivity values ( κ < 4 W m −1 K −1 ) could be maintained. Our results emphasize that phase-separated HH compounds are suitable low cost materials and can lead to enhanced thermoelectric efficiencies beyond the set benchmark for industrial applications.